A Study of Sino-Russian Energy Cooperation from the Perspective of Theories of International Relations - Chaoyue Yang (Journal of China and International Relations, 2013)
Energy cooperation is an important component in the Sino-Russia relationship. After more than a decade of efforts, China and Russia have made great progress in their cooperation in the area of oil and natural gas, which has not only promoted the economic developments in both countries, but also expanded their common interests to a large extent, resulting in a tremendous improvement of the two countries’ international strategies towards each other. Nevertheless, constrained and influenced by the evolution of contemporary international politics and economies, the Sino-Russia energy cooperation is facing some problems and barriers. Therefore, the aim of this article is to analyze the multiple elements affecting the Sino-Russia energy cooperation through the prism of Neo-realism, Neo-liberalism and Social Constructivism, hence a clear account of the opportunities and challenges that constitute this cooperation will be gained.